Ship breaker - Bacigalupi, Paolo (Little, Brown and Co., 2010)
In a futuristic world, teenaged Nailer scavenges copper wiring from grounded oil tankers for a living, but when he finds a beached clipper ship with a girl in the wreckage, he has to decide if he should strip the ship for its wealth or rescue the girl.